Reaction Behavior and Kinetic Model of Hydroisomerization and Hydroaromatization of Fluid Catalytic Cracking Gasoline - Haijun Zhong; Xiwen Song; Shuai He; Xuerui Zhang; Qingxun Li; Haicheng Xiao; Xiaowei Hu; Yue Wang; Boyan Chen; Wangliang Li (Molecules, 2025)
The hydro-upgrading reaction behavior of model compound 1-hexene and FCC middle gasoline was investigated using a fixed-bed hydrogenation microreactor with a prepared La-Ni-Zn/H-ZSM-5 catalyst. The catalyst was prepared by wetness impregnation method, using hydrothermal treated H-ZSM-5 zeolite blended with alumina as the support, and La, Ni, Zn as the active metals. The reaction tests were carried out at 300–380 °C, 1.0 MPa, 1.5–3.0 h−1 (LSHV), and 300:1 v/v (H2/oil). Analyzing the changes in hydrocarbon components before and after hydro-upgrading elucidated the mechanistic pathways of olefin hydroisomerization and hydroaromatization. Based on these findings, a seven-lump kinetic model was established for the FCC middle gasoline hydro-upgrading process. Given the diversity and complexity of reaction products, they were grouped into seven lumps: normal paraffins, isoparaffins, linear olefins, branched olefins, cycloolefins, naphthenes, and aromatics. Kinetic parameters were estimated using the Levenberg–Marquardt algorithm and validated against experimental data. The results showed that the conversion of naphthenes to aromatics exhibited the highest activation energy and pre-exponential factor, resulting in the largest reaction rate increase within the 320–380 °C range. The model accurately predicted the product yields of FCC gasoline hydro-upgrading, with a relative error of less than 5%. These findings provide valuable guidance for the optimization, design, and operation of FCC gasoline hydro-upgrading units, as well as for catalyst development, with the aim of improving process efficiency and fuel quality.